Mortalidade por AIDS e fatores associados no município de Ponta Grossa, Paraná: 2008-2015 (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Mortality by AIDS and associated factors in the city of Ponta Grossa, Paraná, Brazil: 2008-2015